2021
DOI: 10.3846/btp.2021.12774
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior Role in Mediating the Effect of Transformational Leadership on Organizational Performance in Gold Industry of Saudi Arabia

Abstract: This paper mainly aims at investigating the mediating effect of organizational citizenship behaviour in the relationship between transformational leadership behaviour and organizational performance as well as the mediating effect of organizational citizenship behaviour in the relationship between psychological ownership, working environment, employee involvement, incentives, and employee motivation, and organizational performance. To achieve the objectives of the study, quantitative research approach was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The intervening variables are organizational commitment, management control system, leader-member exchange, and organizational citizenship behavior. The researchers have confirmed that the variables mediate the transformational leadership-organizational performance relationship (Patiar & Wang, 2016;Nguyen et al, 2017;Alhashedi, Bardai, Al-Dubai, & Alaghbari, 2021). Moreover, the intervening variables between partnership strategy and organizational performance are partnership commitment and competitive advantage.…”
Section: Introductionmentioning
confidence: 75%
“…The intervening variables are organizational commitment, management control system, leader-member exchange, and organizational citizenship behavior. The researchers have confirmed that the variables mediate the transformational leadership-organizational performance relationship (Patiar & Wang, 2016;Nguyen et al, 2017;Alhashedi, Bardai, Al-Dubai, & Alaghbari, 2021). Moreover, the intervening variables between partnership strategy and organizational performance are partnership commitment and competitive advantage.…”
Section: Introductionmentioning
confidence: 75%
“…In recent years, the OCB concept has received scholarly interest due to its substantial influence on achieving and protecting the organizational competitive advantage (Ali Alhashedi et al, 2021). OCB can be defined as employees' voluntary behavior and actions that are not formally or directly recognized by the organizational total reward system but contribute to overall organizational functioning effectiveness (Organ, 1988) in the extent to which an employee goes beyond the minimum requirement of their legitimate job (Smith et al, 1983).…”
Section: Literature Review and Hypothesis Development Organizational ...mentioning
confidence: 99%
“…The HRM practices that contribute to employee commitment in one organization and management style may not be valid in another country's organization with a different decisionmaking style (Hyun & Oh, 2011). The research studies infer that HRM practices lead to firms' financial and non-financial performance (Ahakwa, Yang, Agba Tackie, & Asamany, 2021;Katou & Budhwar, 2006), employee commitment, and service recovery performance (Mihardjo et al, 2020), transformational leadership behavior, and employee motivation (Alhashedi, Bardai, Al-Dubai, & Alaghbari, 2021). A broad group of writing exists investigating the effect of these HR practices (compensation and empowerment) on HR outcomes (organizational commitment) and examining any interceding role of these HR outcomes on organizational performance in developed nations.…”
Section: Introductionmentioning
confidence: 97%
“…This appropriate interference in HRM practices and procedures is expected to generate an extensive body of research and implications. However, the author found very few studies in the Saudi context investigating aspects related to organizational performance, organizational citizenship, working environment, and employee involvement (Alhashedi et al, 2021). Further, Alhashedi et al (2021) discussed the impact of HRM practices (i.e., employee incentives and motivation) on organizational knowledge management, learning, and culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation